Սենեքերիմ Տէր-Յակոբեան՝ պետականացուած Մատենադարանի առաջին տնօրէնը - Տէր-Վարդանեան, Գէորգ (Մատենադարան)
Two articles concerning the first director of Mashtots Matenadaran, Senek‘erim Ter-Hakobyan (1881–1938, director in 1921–1938), appeared in the 1953 issues of the Armenian magazine Hairenik published in Boston during 1922–1970. One of the publications is signed “S. Guryan,” and the author of the second is the famous collector and philologist Harut‘yun K‘yurtian (1901–1976), who lived the most part of his life (1923–1976) in the USA. The articles describe the personality of Senek‘erim Ter-Hakobyan, his unique human character and his high intellect. K‘yurtian’s article depicts the terrible atmosphere of fear, suspicion and snitching prevailing in Matenadaran in 1931. However, thanks to the principled and selfless attitude of Senek‘erim Ter-Hakobyan, Matenadaran survived that difficult time without manuscript losses. This happened also thanks to K‘yurtian’s efforts, who convinced the Bolshevik officials that Armenian manuscripts had no value in overseas markets and auctions and therefore were useless for sale. Автор публикации обнаружил в номерах 1953 года журнала "Айреник" (Бостон, 1922-1970 гг.) две статьи о первом директоре Матенадарана имени Маштоца Сенекериме Тер-Акопяне (1881-1938 гг., в директор 1921-1938 гг.). Одна подписана "С. Гурян", автор же второй статьи – известный коллекционер и филолог Арутюн Кюрдян (1901-1976), проживший большую часть своей жизни (1923-1976) в США. В статье рассказывается о личности Сенекерима Тер-Акопяна, его уникальных человеческих чертах, а также о его высоких интеллектуальных качествах. А. Кюрдян в своей статье описывает ужасную атмосферу страха, подозрительности и доносительства, царившую в Матенадаране в 1931 г. Однако благодаря принципиальной и самоотверженной позиции Сенекерима Тер-Акопяна, Матенадаран пережил эти трудные времена, не потеряв ни одной рукописи. Кюрдян тоже способствовал важному делу сохранения рукописей, убедив большевистских чиновников, что армянские рукописи не имеют цены и не продаются на зарубежных рынках и аукционах древностей.
Keywords: Մատենադարանի պատմություն